Influence of thermal and thermomechanical stimuli on a molar tooth treated with resin-based restorative dental composites. Issue 5 (May 2022) - Thadathil Varghese, Jerrin; Babaei, Behzad; Farrar, Paul; Prentice, Leon; Prusty, B. Gangadhara
Abstract: Objectives: In-vivo experimental techniques to understand the biomechanical behavior of a restored tooth, under varying oral conditions, is very limited because of the invasive nature of the study and complex tooth geometry structure. Therefore, 3D-Finite element analyses are used to understand the behavior of a restored tooth under varying oral conditions. In this study, the distribution of maximum principal stress (MaxPS) and the location of MaxPS on a restored tooth using six different commercially available dental resin composites under the influence of thermal and thermomechanical stimuli are performed. Methods: An intact tooth was scanned using µ-CT and segmented to obtain separate geometric models of the tooth, including enamel and dentine. Then, a class II mesial-occlusal-distal (MOD) cavity was constructed for the tooth model. The restored tooth model was further meshed and imported to the commercial Finite Element (FE) software ANSYS. Thermal hot and cold stimuli at 50 °C and 2 °C, respectively, were applied on the occlusal and lingual surface of the tooth model with the tooth's ambient temperature set at 37 °C. A uniform loading of 400 N was applied on the occlusal surface of the tooth to imitate the masticatory forces during the cyclic thermal stimuli. Results: The results of this study showed that the restorative materials with higher thermal conductivity showed a lower temperature gradient between the restoration and enamel, during the application of thermal stimuli, leading to a higher value of MaxPS on the restoration. Moreover, on applying thermal stimuli, the location of MaxPS at the restoration-enamel junction (REJ) changes based on the value of the coefficient of thermal expansion (CTE). The MaxPS distribution on the application of simultaneous thermal and mechanical stimuli was not only dependent on the elastic modulus of restorative materials but also their thermal properties such as the CTE and thermal conductivity. The weakest part of the restoration was at the REJ, as it experienced the peak stress level during the application of thermomechanical stimuli. Significance: The findings from this study suggest that restorative materials with lower values of elastic modulus, lower coefficient of thermal expansion and higher values of thermal conductivity result in lower stresses on the restoration. The outcomes from this study also suggest that the thermal and mechanical properties of a restorative material can have a considerable effect on the selection of restorative materials by dental clinicians over conventional restorative materials. Graphical Abstract: ga1 Highlights: A replicable methodology for segmenting µ-CT images, using thresholding and manual multiple slice editing, was described. A class II mesial-occlusal-distal cavity was designed for the 3D model of the tooth generated from the µ-CT data. The thermal and mechanical responses of the modeled tooth, using six different restorative materials were investigated. The location of maximum principal stresses for the restored tooth at the restoration-enamel interface were reported.